Progress of Ginsenoside Rb1 in neurological disorders - Ling, Gongxia; Zhang, Min; Chen, Chizhang; Wang, Yan; Gao, Qiqi; Li, Jianshun; Yuan, Hao; Jin, Wenwen; Lin, Wei; Yang, Lingrong (Frontiers in Pharmacology, 2024)
Ginseng is frequently used in traditional Chinese medicine to treat neurological disorders. The primary active component of ginseng is ginsenoside, which has been classified into more than 110 types based on their chemical structures. Ginsenoside Rb1 (GsRb1)—a protopanaxadiol saponin and a typical ginseng component—exhibits anti-inflammatory, anti-oxidant, anti-apoptotic, and anti-autophagy properties in the nervous system. Neurological disorders remain a leading cause of death and disability globally. GsRb1 effectively treats neurological disorders. To contribute novel insights to the understanding and treatment of neurological disorders, we present a comprehensive review of the pharmacokinetics, actions, mechanisms, and research development of GsRb1 in neurological disorders (Graphical abstract).